2016
DOI: 10.1101/088328
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural and functional brain changes following four weeks of unimanual motor training: evidence from fMRI-guided diffusion MRI tractography

Abstract: We have reported reliable changes in behaviour, brain structure and function in 24 healthy right-handed adults who practiced a finger-thumb opposition sequence task with their left hand for 10 mins daily, over four weeks. Here we extend these findings by employing diffusion MRI to investigate white-matter changes in the corticospinal tract, basal-ganglia, and connections of the dorsolateral prefrontal cortex. Twenty-three participant datasets were available with pre-training and post-training scans. Task perfo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…270 Behavioural improvements and anatomical homogeneity in this study were greater is typically reported in trials of CP therapy. within the bounds of an approval originally granted by the University of Queensland Human Research Ethics Committee, for which participants gave written informed consent.…”
Section: %supporting
confidence: 53%
See 4 more Smart Citations
“…270 Behavioural improvements and anatomical homogeneity in this study were greater is typically reported in trials of CP therapy. within the bounds of an approval originally granted by the University of Queensland Human Research Ethics Committee, for which participants gave written informed consent.…”
Section: %supporting
confidence: 53%
“…Participant numbers were independently calculated to achieve an 80% power of detecting a significant difference Due to the dearth of literature reporting diffusion changes observed in children with CP undergoing longitudinal therapy, the amounts of expected longitudinal change were based on a healthy adult ('HA') dataset from a recent study, in which 24 healthy adults practiced a novel finemotor task with their non-dominant hand for ten minutes a day for four weeks. 270 This study found substantial improvements in task performance that were accompanied by changes in functional MRI, cortical thickness (voxel-based analysis), TMS maps and the delineated corticospinal tract FA in the 'trained' hemisphere. Importantly, in this study, both ROI seeded tractography and surface-fMRI seeded tractography were conducted.…”
Section: Diffusion Mri Tractographymentioning
confidence: 98%
See 3 more Smart Citations